Cerebrospinal fluid findings in patients with myelin oligodendrocyte glycoprotein (MOG) antibodies. Part 1: results from 163 lumbar punctures in 100 adult patients - Jarius, Sven; Korporal-Kuhnke, Mirjam; Haas, Jürgen; Wildemann, Brigitte (Journal of neuroinflammation, 2020)
New-generation cell-based assays have demonstrated a robust association of serum autoantibodies to full-length human myelin oligodendrocyte glycoprotein (MOG-IgG) with (mostly recurrent) optic neuritis, myelitis, and brainstem encephalitis, as well as with neuromyelitis optica (NMO)-like or acute-disseminated encephalomyelitis (ADEM)-like presentations. However, only limited data are yet available on cerebrospinal fluid (CSF) findings in MOG-IgG-associated encephalomyelitis (MOG-EM; also termed MOG antibody-associated disease, MOGAD). To describe systematically the CSF profile in MOG-EM. Cytological and biochemical findings (including white cell counts and differentiation; frequency and patterns of oligoclonal bands; IgG/IgM/IgA and albumin concentrations and CSF/serum ratios; intrathecal IgG/IgA/IgM fractions; locally produced IgG/IgM/IgA concentrations; immunoglobulin class patterns; IgG/IgA/IgM reibergrams; Link index; measles/rubella/zoster (MRZ) reaction; other anti-viral and anti-bacterial antibody indices; CSF total protein; CSF l-lactate) from 163 lumbar punctures in 100 adult patients of mainly Caucasian descent with MOG-EM were analyzed retrospectively. Most strikingly, CSF-restricted oligoclonal IgG bands, a hallmark of multiple sclerosis (MS), were absent in almost 90% of samples (N = 151), and the MRZ reaction, the most specific laboratory marker of MS known so far, in 100% (N = 62). If present, intrathecal IgG (and, more rarely, IgM) synthesis was low, often transient and mostly restricted to acute attacks. CSF WCC was elevated in > 50% of samples (median 31 cells/μl; mostly lymphocytes and monocytes; > 100/μl in 12%). Neutrophils were present in > 40% of samples; activated lymphocytes were found less frequently and eosinophils and/or plasma cells only very rarely (< 4%). Blood-CSF barrier dysfunction (as indicated by an elevated albumin CSF/serum ratio) was present in 48% of all samples and at least once in 55% of all patients (N = 88) tested. The frequency and degree of CSF alterations were significantly higher in patients with acute myelitis than in patients with acute ON and varied strongly depending on attack severity. CSF l-lactate levels correlated significantly with the spinal cord lesion load in patients with acute myelitis (p < 0.0001). Like pleocytosis, blood-CSF barrier dysfunction was present also during remission in a substantial number of patients. MOG-IgG-positive EM is characterized by CSF features that are distinct from those in MS. Our findings are important for the differential diagnosis of MS and MOG-EM and add to the understanding of the immunopathogenesis of this newly described autoimmune disease.